Estrategias metodológicas para mejorar el proceso enseñanza aprendizaje del área de ciencias naturales de los estudiantes de octavo, noveno y décimo grados del subnivel de básica superior, de la unidad educativa municipal Héroes del Cenepa, del cantón y provincia de Loja. Periodo lectivo 2013-2014 - Padilla Alvear, Lucas Valentin (2015)
This research deals with methodological strategies to improve the teaching-learning process in the area of Natural Sciences students in eighth, ninth and tenth grades Sublevel Basic Higher of Unidad Educativa Municipal Héroes del Cenepa. Academic Period 2013-2014, for which we worked with the following general objective is to propose several active learning strategies to improve the teaching of Natural Sciences students at eighth, ninth and tenth grades of Unidad Educativa Municipal Héroes del Cenepa Sublevel Basic Higher. Academic period 2013-2014, it helped me to verify the process of learning of Natural Sciences, skills, abilities, knowledge, and habits to use learning strategies; likewise the following scientific, analytical, deductive, descriptive to go elucidating the different research approaches and go corroborating its postulates methods were used; we worked with the following talent 26 students and one teacher, to which was applied a structured survey to corroborate through questions about learning and strategies to be applied in the area of Natural Sciences. From all this research work it is concluded that the teacher does not apply different methodological strategies for teaching in the area of Natural Sciences.